Transitory O-rich chemistry in heavily obscured C-rich post-AGB stars. Issue 5 (July 2016) - García-Hernández, D. A.; García-Lario, P.; Cernicharo, J.; Engels, D.; Perea-Calderón, J. V.
Abstract: Spitzer/IRS spectra of eleven heavily obscured C-rich sources rapidly evolving from asymptotic giant branch (AGB) stars to Planetary Nebulae are presented. IRAM 30m observations for three of these post-AGBs are also reported. A few (3) of these sources are known to exhibit strongly variable maser emission of O-bearing molecules such as OH and H2 O, suggesting a transitory O-rich chemistry because of the quickly changing physical and chemical conditions in this short evolutionary phase. Interestingly, the Spitzer/IRS spectra show a rich circumstellar carbon chemistry, as revealed by the detection of small hydrocarbon molecules such as C2 H2, C4 H2, C6 H2, C6 H6, and HCN. Benzene is detected towards two sources, bringing up to three the total number of Galactic post-AGBs where this molecule has been detected. In addition, we report evidence for the possible detection of other hydrocarbon molecules like HC3 N, CH3 C2 H, and CH3 in several of these sources. The available IRAM 30m data confirm that the central stars are C-rich - in despite of the presence of O-rich masers - and the presence of high velocity molecular outflows together with extreme AGB mass-loss rates (∼⃒10 -4 Mʘ /yr). Our observations confirm the polymerization model of Cernicharo [1] that predicts a rich photochemistry in the neutral regions of these objects on timescales shorter than the dynamical evolution of the central HII region, leading to the formation of small C-rich molecules and a transitory O-rich chemistry.